Characteristics of Diabetes Mellitus with Diabetic Neuropathy at Cut Meutia Hospital - Khairunnisa, Khairunnisa; Maulina, Nora; Ramadhansyah, Fitriana (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Diabetic neuropathy is a complication in the form of nerve damage that often occurs in patients with diabetes mellitus, which is 50% of sufferers. Nerve complications can cause a decrease in quality of life and other complications. This study aims to determine the characteristics of nerve damage that occurs in diabetes mellitus patients at Cut Meutia Hospital. The type of research used in this study was a non-experimental quantitative descriptive study taken through medical records and patient status from 43 people. Respondents were selected using a total sampling technique. Analysis of data was performed by univariate analysis. The results showed that the most age who experienced DM neuropathy was the middle age category, 46-59 years old and there were 20 people (46.51%). The gender that experienced DM neuropathy most in this study was male with 22 people (51.16%). Peripheral neuropathy is the most common type of neuropathy in this study which was experienced by 24 people (55.81%).